MATHEMATICAL MODELING OF EXPERIMENTS PLANNING - Bosov, A. A.; Artemchuk, V. V. (Science and Transport Progress, 2008)
In the article the results of theoretical researches aimed at the mathematical design of planning the experiments are presented. The new is that planning the experiments is conducted simultaneously on three indices of quality. They are coverage-to-basis strength of adhesion, wearproofness and coverage thickness. Development of mathematical design of planning the experiment on a few indices enables decreasing a quantity and cost of experiments.